A Highly Sensitive CMOS Digital Hall Sensor for Low Magnetic Field Applications - Li Li; Hong-Bin Pan; Shu-Zhuan He; Yue Xu (Sensors, 2012)
Integrated CMOS Hall sensors have been widely used to measure magnetic fields. However, they are difficult to work with in a low magnetic field environment due to their low sensitivity and large offset. This paper describes a highly sensitive digital Hall sensor fabricated in 0.18 μm high voltage CMOS technology for low field applications. The sensor consists of a switched cross-shaped Hall plate and a novel signal conditioner. It effectively eliminates offset and low frequency 1/f noise by applying a dynamic quadrature offset cancellation technique. The measured results show the optimal Hall plate achieves a high current related sensitivity of about 310 V/AT. The whole sensor has a remarkable ability to measure a minimum ±2 mT magnetic field and output a digital Hall signal in a wide temperature range from −40 °C to 120 °C.